Synthesis of polymer nanoparticles sensitive to pH for DNA delivery in intracellular environment - Lopes, Eduardo (2013)
Dissertação de mest., Ciências Biomédicas, Departamento de Ciências Biomédicas e Medicina, Univ. do Algarve, 2011